La arquitectura jesuítico-guaraní : una experiencia de interacción cultural - Levinton, Norberto, (Paradigma indicial. Serie Historia americana., 2008)
Ethnological and anthropological studies of the architecture of the 17th century Jesuit guarani missions in Argentina, in what the author considers archaeological evidence of the integration of the European and Guaran structural concepts of space and typology in the construction of the missions. The study of the ruins located in the province of Misiones in the northeastern region of Argentina confirm how the use of colonial science left, amongst other practices the participation and professionalization of the guaran Indians in the skilled activities of the colonial society, including the construction of buildings.